Patient Health Questionnaire (PHQ-9): a systematic review and a meta-analysis of reliability generalization - Ortiz Morán, Mafalda (2024)
Depression is a significant public health problem, which makes it necessary to understand the psychometric properties of the instruments used for its evaluation to facilitate better decision-making. The Patient Health Questionnaire (PHQ-9) is an instrument that achieves optimal accuracy levels in measuring depression. Therefore, the objective of this study was to conduct a meta-analysis to generalize its reliability. A systematic search conducted in Web of Science and Scopus between 2020 and 2022 retrieved 32 studies that applied the PHQ-9 and reported Cronbach's alpha. A random effects meta-analysis was performed to estimate the test reliability, while heterogeneity was assessed using Cochran's Q and I2 statistics. Potential moderating variables were examined through meta-regression and subgroup analyses. The combined reliability of the PHQ-9 was 0.846 (95% CI: 0.824-0.862). The Egger test and Kendall’s τ rank correlation test indicated no significant evidence of publication bias in the evaluated data. Also, there was also statistically significant heterogeneity in the total sample, determined by the Q test and the I2 variability index. The meta-regression analysis showed that the type of sample (clinical vs. general) is a statistically significant moderator. This meta-analytical study demonstrates that the PHQ-9 has good internal consistency and is suitable for research purposes.